Analisis Infrastruktur Teknologi Informasi pada BMSTV dengan Pendekatan SWOT dan Value Chain - Siska Nathasia; Nur Kholifah Dwi Prasetyo Kartika; Yuana Premasiwi; Berliana Zahrah Nursyifa; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of information technology requires local television stations to have well-managed and effective IT infrastructure. BMSTV, as a local television station, faces challenges in adapting to digital broadcasting and competition from digital media platforms. This study aims to analyze the condition of information technology infrastructure at BMSTV and to formulate strategic development recommendations using SWOT and Value Chain approaches. The research method employed is a qualitative descriptive approach using secondary data obtained from organizational documents and literature studies. The results indicate that BMSTV has strengths in basic technology utilization and local content, but faces weaknesses in system integration and IT human resource competencies. Media digitalization presents significant opportunities to improve service quality, while digital media competition poses major threats. This study recommends strengthening IT infrastructure, enhancing human resource competencies, and developing integrated information systems.